Desenvolvimento de processo de validação de firmware de um analisador de energia - Bittencourt, Martin Günter Borchardt (Universidade do Vale do Rio dos Sinos, 2015)
In the current scenario of the software industry, increasingly companies invest in improving the quality of their products in order to obtain better technical and commercial results. Part of these efforts focus on the establishment of developmental processes, one of these being the validation process that allows to conclude, by applying an organized series of tests, if the created product is one that is intended to get under project's scope. This article presents the development of a validation process in accordance to the CMMI-Dev 1.3 model validation process for the user interface firmware of a power quality analyzer. Not only the process received full approval, but this work also culminated in the creation of a new test case management tool.
Keywords: Desenvolvimento de processo de validação; Implantação de processo de validação; Validação de Firmware; Analisador de energia; Indústria de software; Software industry; Validation process; Developmental processes